Osaamisperustaisen kilpailukyvyn ja yrittäjyyden edistäminen : tutkimustapauksena Raahen tietotekniikan muuntokoulutusohjelma insinööreille - Koivunen, Mauri (2004)
The strong surge in information technology in the 1990’s resulted in a scarcity of skilled employees and a growing need to develop the employees’ competence. Professional degree upgrading is a quick and flexible method of meeting the training and competence needs of working life. Upgrading a prior degree to a degree at a higher level is a form of adult training. This study deals with higher degrees in information technology. This study aims to illustrate the effects of upgrading training on individual competencies and their advancement, success at work, entrepreneurial skills and increasing the competence-based competitiveness of companies. The research focused on the upgrading training of individuals with prior degrees in engineering launched in Raahe in 1990. The theoretical framework of the study consisted of three main themes: competence, competitiveness and entrepreneurship. The main concepts were operationalised within the framework to be empirically tested. Case study and quantitative approaches were chosen as research strategies, the latter of which was further supplemented with qualitative aspects. The empirical results were based on self-evaluation by the participants. The evaluation of the effects of the training focused on certain areas of competence which are of importance for the competence-based success of individuals and companies. In addition, the research concentrated on the effects of the training as factors to increase enterprise and to promote entrepreneurship. 57 students graduated from the Raahe training programme between the years 1992 and 2000, of whom 36 completed the questionnaire. Normal distribution, average, median and mode were then calculated. The variables were divided into categories according to the areas of competence, based on a model compatible with the theoretical framework. Factor analysis was used to examine the loading of the variables by categories. Furthermore, gap analysis was employed to demonstrate the differences between the demands of working life and the skills provided by the training. The results were used to calculate the correlation between variables and groups of variables and to examine the causality between variables with regression analysis. Based on the research results, professional upgrading provided the participants with all the necessary professional skills in the areas emphasised in the training: information technology, data communications, electronics, electrical and automatic control engineering, mathematics, natural sciences and English. However, in other areas of importance in working life, such as leadership and management, human relations, practices of working life and other personal attributes, the training did not enhance the participants’ competence to any great extent. The training augmented the competitiveness of individuals and companies by improving competence, motivation, enterprise and abilities to work independently, but had little effect on the development of entrepreneurship and attitudes. However, the development of competence, innovativeness, motivation and enterprise contributed indirectly to promoting entrepreneurship. According to the results, professional degree upgrading equipped the participants mostly with mathematical and natural science skills. Therefore, the training responded to the needs of working life by overemphasizing technocratic substance and thus failed to allow sufficient scope for general knowledge and social and entrepreneurial skills in the development of individuals’ overall competencies.